Proceedings of the Fourth Meeting of the EURO Working Group on Operational Research (OR) in Agriculture and Forest Management (EWG-ORAFM) - Sandars, D. L.; Pla, L. M. (Cambridge University Press, 2009)
The current paper will survey how things have changed over nearly 50 years of OR applied to agriculture. The first ‘OR group’ was set up at the National Institute of Agricultural Engineering by Dan Boyce in 1969 and is now at Cranfield University. The current paper will examine how, and what, factors have influenced the type of work and the methods used. What applications have stood the test of time and what are just distant memories in paper publications?